Did the Great Recession Affect Sex Ratios at Birth for Groups with a Son Preference? - Soohyung Lee; Chiara Orsini (Institute of Labor Economics (IZA), 2017)
This paper examines the extent to which the Great Recession affected gender composition at birth. We focus on ethnic minorities in the US known for a son preference Chinese, Indians, and Koreans. Using the DID method, we find that in response to the Great Recession, the fraction of newborn boys increased among Chinese Americans. Our results suggest that a cultural norm, namely son preference, may be directly affected by economic conditions.
Keywords: J1; I1; 330; son preference; Great Recession; missing girls; sex ratios; fertility